(untitled) (Islamic Sciences Journal, 2023)
It is known that the Arabic language abounds with various words and words meanings and semantics born proved to scientists The practice of languages ​​The Arabic language Bmhaha, grammar and rhetoric is one of the most significant languages. And that mission of Hardworking: is the confusion of the provisions of its origins.The work of the mujtahid is the jurisprudence and understanding of the text, since the text cannot be deduced from the judgment unless: - A - realize the meaning. B - knew the word goal and meaning. (C) Show how it is indicative of governance and quality This significance and degree. Understanding of the text depends on: 1- Knowledge of the methods of statement in the Arabic language. 2 - ways to indicate the meaning. 3 – and what is indicated by the words singular and complex. For this reason, scientists have established rules and regulations that are in fact derived from: The nature of the Arabic language as their use in the meanings as decided by the imams of the language according to the tracing and extrapolation of the Arabic methods, They are not special legal or religious bases, but are Arab in form and subject matter of spirit and text. One of these rules is the rule of Aleqteda indication at the Hanafi: is the indication of untold speech that the truth of the speech, its honesty or the validity of the legitimacy depends on it. The wording of the text does not indicate the untold ,But rather twofold the validity of speech in accordance with the act, or legitimately appreciated, and called this Aleqteda indication , as appropriate, because it means calling and demand. The meaning of the speech is demanded and called by the sincerity of speech, or his honest .When the research needed to determine the nature of the relationship between fundamentalist and linguistic The words and their meaning to work by the text to develop an understanding of the text. The fundamentalist Hanafi and Shafi’i fundamentalists make the omitted from the type of Muqtada ,while the late fundamentalists are separated between them .This necessitated a difference in the general estimated or not, if we return to the sources of fundamentalism we´ll find that some of them said by Muqtada and the others are denied it. In Fact the rule of Aleqteda Indication is based on the Hanafi on what indicates the word “Muqtada” as a language, and it is the request. Hence the (text) of the fundamentalists may need to complete it with the meanings and words, so that they called Aleqteda or the requirement of the text. This is what I tried hard to show and decipher. And solve its dilemmas in my modest research.